Waste Management in Batu City through the Perspective of Good Environmental Governance - Muhammad Wahyu Prasetyo Adi; Romy Hermawan; Mardiyono Mardiyono; Kamila Khoirunnisa (JURNAL ILMU SOSIAL, 2025)
The waste polemic in Batu City requires waste management at the village level. TPS 3R Temas Sae and TPS 3R Dadaprejo are the result of government policies in recent years. Both of these TPS 3Rs have the potential for development to create ideal governance. The purpose of this study is to compare the current governance systems in the waste reduction process. Through a qualitative approach with descriptive type, this research analyzed and reviewed the comparison results based on the concept of good environmental governance. Furthermore, the results of this study state that TPS 3R Temas Sae and TPS 3R Dadaprejo have their own advantages and disadvantages. Both multi-level interaction aspects are still weak in establishing cooperation with private actors. While the aspect of policy internalization is still the same around the problem of low capacity and capability of the workforce in reading internal needs. And related to sustainable development TPS 3R Temas Sae excels in more innovative processing results, ranging from processing into bar soap, processed mangosteen, organic fermented medicine, maggot cultivation, cat feed, fish feed to organic fertilizer. While TPS 3R Dadaprejo is in the form of maggot and compost. However, TPS 3R Dadaprejo has approved the SI PAPAH application as an information center to retribution